A dynamic queue protocol for multiaccess wireless networks with multipacket reception. - Qing Zhao (IEEE Transactions on wireless communications)
A dynamic medium access control (MAC) protocol is proposed for a finite-user slotted channel with multipacket reception (MPR). This protocol divides the time axis into transmission periods (TPs) where the ith TP is dedicated to the transmission of the packets generated in the (i-1)th TP. At the beginning of each TP, the state (active or idle) of each user is estimated based on the length of the previous TP and the incoming traffic load. By exploiting the information on the state of users and the channel MPR capability, the number of users who can simultaneously access the channel in the current TP is chosen so that the expected length of this TP is minimized. As a result, the MPR capability is more efficiently utilized by the proposed protocol as compared to, for example, the slotted ALOHA with optimal retransmission probability. Furthermore, the proposed protocol requires little online computation. Its simplicity is comparable to that of slotted ALOHA. It can be applied to random access networks with spread spectrum and/or antenna array.